Genetic analysis of four main flavonoids in barley grain (Bangladesh Journal of Botany, 2019)
Genetic analysis of 4 major flavonoids in barley interspecific hybrids which were used as parents for half diallel crossingwas carried out. Compared with seven parents, the highest general combining ability of catechin content was Clipper barley, the higest general combining ability (GCA) of myricetin content were Schooner barley and Huangchangguang barley, the highest general combining ability of quercetin content were Ziguangmang barley and Kuanying barley, the highest general combining ability of kaempferol content were Ziguangmang barley and Schooner barley, the highest general combining ability of flavonoids are Schooner barley and Huangchangguang barley. The hybrid combination of a good matching were Clipper barley, Schooner barley, Ziguangmang barley and Kuanying barley, as a comprehensive general combining ability, specific combining ability, and combinations of which can be used as flavonoids in barley breeding.